Using Student Profiles to Motivate and Understand How to Attract Women to Computer Science - Marín Raventós, Gabriela (2020)
This article reports how to build and analyze student profiles to influence the perception that girls and young women have of the profession, and of the diverse work opportunities that exist in Computer Science in Costa Rica. The data presented corresponds to a broader work of the European-Latin American project called W-STEM, which also involves other STEM disciplines. The obtained results from the survey to build the profiles are analyzed. The most significant gender difference is in terms of a lower female self-perception of abilities before starting undergraduate studies, compared to the male counterpart. Fortunately, this difference disappears for female at graduate level.